Trait based assessment in seedling stage of rice for salinity tolerance - Thomas, Tinu; Anusuya, Natarajan; Purushothaman, Jayaraman; Janarthanan, Raja; Karthick, Jothiganapathy; Nadaradjan, Subbarayan; Thirumeni, Saminadane (Journal of Cereal Research, 2022)
Breeding for salinity tolerance is the need of the hour and identifying the potential donors and sources is very crucial. Hence, screening for the genotypes or lines by assessing the physiological and morphological traits are vital for identifying the tolerant genotypes. The lines identified in this study can be used for trait-based breeding for improving salinity tolerance in rice.